Autoethnography of Two Teachers in the Beginnings of Distance Education in 2020 Pandemic - Fendández Poncela, Ana María (2022)
The central objective of this text is an approach to the experiences and experiences, to the feelings and reflections of the practice of teaching in times of remote education that surprisingly imposed the SARS-CoV-2 pandemic that causes COVID-19 in the year 2020. This is done with a general introduction on psychological issues and on social research. Then, we delve into and deepen around online education through vivid personal stories of two teachers in the times of the coronavirus pandemic and distance education in Mexico. One from a private basic education school and the other from a public university, however, coincide in the perceptions, sensations and emotions of great stress, and in the need for rest, as well as a reevaluation of the work situation, and even personal.